From inclusive identities to inclusive societies: comparing the content, structure, and impact of all inclusive superordinate categories - Lima, Margarida Gil de Figueiredo Carmona e (2022)
This work focused on the ontology of all-inclusive superordinate categories (encompassing all human beings) and their role in building more inclusive societies. Eight studies examined their content, structure, and impact on intergroup relations. Regarding content, a qualitative study showed that global citizenship-oriented labels (e.g., “citizens of the world”) and humanness-oriented labels (e.g., "all humans everywhere") activated different prototypical meanings (Chapter 2). Regarding structure, five studies relying on a prototype approach demonstrated that "citizens of the world" has a prototypical structure and there is differentiated cognitive processing for its central and peripheral attributes (Chapter 3). Two studies compared how “citizens of the world” and “humans” are cognitively represented (Chapter 4). A correlational study showed that national citizens perceived migrants as more prototypical of "citizens of the world" (outgroup projection); whether no projection occurred for "humans". An experimental study showed that the salience of “humans” (vs. “citizens of the world”) triggered higher entitativity and essentialist perceptions, and dual-identity representations. Regarding impact, these studies explored intergroup helping from host communities towards migrants (Chapter 4). Identification with "citizens of the world" and with “humans” was associated with different patterns of helping (dependency- and autonomy-oriented help); whether no differences on intergroup helping were found when categories’ salience was manipulated. Overall, results suggest that all-inclusive superordinate categories represent different socio-psychological realities (i.e., content, structure, and impact), and their differentiated spontaneous prototypical meaning, and particularly the malleability of their prototypes to contextual socio-status-political motivations, might have an important role in their effectiveness as common ingroup identities.